2000
DOI: 10.4049/jimmunol.164.1.350
|View full text |Cite
|
Sign up to set email alerts
|

Convergence of Fcγ Receptor IIA and Fcγ Receptor IIIB Signaling Pathways in Human Neutrophils

Abstract: Human neutrophils (PMNs) express two receptors for the Fc domain of IgG: the transmembrane FcγRIIA, whose cytosolic sequence contains an immunoreceptor tyrosine-based activation motif, and the GPI-anchored FcγRIIIB. Cross-linking of FcγRIIIB induces cell activation, but the mechanism is still uncertain. We have used mAbs to cross-link selectively each of the two receptors and to assess their signaling phenotypes and functional relation. Cross-linking of FcγRIIIB induces intracellular Ca2+ release and receptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 85 publications
3
67
0
1
Order By: Relevance
“…3A). These findings corroborate and extend previous studies documenting high valency immune complexes to activate PMN primarily via Fc␥RIIIb (44,45,48). Furthermore, IgA-opsonized B. pertussis was taken up efficiently via interaction with Fc␣RI and induced PMN respiratory burst activity.…”
Section: Discussionsupporting
confidence: 81%
“…3A). These findings corroborate and extend previous studies documenting high valency immune complexes to activate PMN primarily via Fc␥RIIIb (44,45,48). Furthermore, IgA-opsonized B. pertussis was taken up efficiently via interaction with Fc␣RI and induced PMN respiratory burst activity.…”
Section: Discussionsupporting
confidence: 81%
“…As GPI-anchored proteins are enriched in DRMs, this result suggests that signaling is enhanced through recruitment of rafts to clusters of transmembrane Fc␥R. In further support of that conclusion, when the GPIanchored Fc␥R was clustered using antibodies specific for that form of the protein, the transmembrane Fc␥R associated with the clusters (65). Another study showed that GM1 (taken as a raft marker) polarizes to the site of contact between natural killer lymphocytes and their target cells in a cholesterol-dependent manner (66).…”
Section: Minireview: Membrane Rafts 17223supporting
confidence: 58%
“…It has been recently proposed that, upon cross-linking by immunoglobulin ligands, Fc␥RIII receptors would recruit Fc␥RII receptors in "signaling raft-like" membrane domains and allow the clustering of ITAMS (Chuang et al, 2000).…”
Section: Ib1 Phagocytosismentioning
confidence: 99%